The Correlation between Total Alkaline Phosphatase and Osteocalcin Levels in Systemic Lupus Erythematosus Patients - Ahmad Mulyadi Sunarya; MI. Diah Pramudianti; Yuwono Hadisuparto (Indonesian Association of Clinical Pathologist and Medical laboratory, 2022)
Systemic Lupus Erythematosus (SLE) is a chronic autoimmune inflammatory disease with various complications, including osteoporosis. However, Bone Mineral Density (BMD) examination, a gold standard for diagnosing and monitoring osteoporosis, is static. Alkaline phosphatase (ALP) is a membrane-bound glycoprotein that catalysis the hydrolysis of monoester phosphate. Osteocalcin (OC) is a non-collagenic bone protein that binds calcium and phosphate, which are both dynamic bone formation activity markers. This study analyzes the correlation between total ALP and OC serum levels in SLE patients. A cross-sectional observational analytic study was conducted in the Clinical Pathology Installation of Dr. Moewardi Hospital Surakarta in June 2020. The subjects were SLE patients receiving Methylprednisolone (MEP) therapy ≥1 year. Data distribution normality test by Saphiro-Wilk, comparative analysis with unpaired T-test, degree of correlation strength between research variables by Pearson correlation test. There were 41 female subjects, and comparative analysis of total ALP and serum OC levels were not significantly different in inactive and active SLE (ALP p=0.373, serum OC p=0.700). Total ALP and serum OC was found to have a weak positive correlation in all SLE patients (r=0.337; p=0.031), a moderate positive correlation in active SLE (r=0.426; p=0.043), while in inactive SLE there was no significant correlation (r=0.247; p=0.324). There is a significant moderate positive correlation between total ALP and serum OC in SLE patients. Total ALP and serum OC examinations are necessary for osteoporosis screening in SLE patients with > 1-year glucocorticoid (GC) therapy.